Transformations of the self: a narrative and poetic based autoethnography. Issue 4 (1st October 2016) - Maurino, James P.
ABSTRACT: This autoethnography explores the phenomenology of both the self and masculinities in a poetic and narrative inquiry. Using an autoethnographic approach as a legitimate means of documenting personal change is discussed. Additionally, the validity of writing, and poetry specifically, as inquiry and transformation is addressed. Its overall purpose is to document and explore changing modes of selfhood and masculinity through the use of original poems and accompanying narrative reflections about them. I hope to demonstrate, through the use of poems as data, that significant change can be accompanied by the act of writing poetry, and that such change has a developmental nature.